Konflik Tanah dan Dampaknya Terhadap Aktivitas Pacu Kuda di Gelanggang Dang Tuanku Batusangkar (2017-2023) - Fallah, Iffah Nurul; Erniwati, Erniwati (Jurnal Kronologi, 2025)
The land conflict between Nagari Baringin and Nagari Saruaso in the Gelanggang Dang Tuanku Bukit Gombak area, Batusangkar, has become a major concern within Minangkabau society, as it affects the continuity of horse racing as an alek nagari (traditional village event) that embodies cultural values and social functions in Tanah Datar Regency. This study examines how the conflict influences horse racing activities by applying the historical method, consisting of heuristics, source criticism, interpretation, and historiography. During the heuristic stage, the researcher collected archives, nagari maps, local news articles, previous studies, books, and other official sources, and conducted field observations and interviews with the Head of Jorong, the Ninik Mamak of Bukit Gombak, Baringin and the Wali Nagari, the KAN of Saruaso. The findings indicate that Gelanggang Dang Tuanku Bukit Gombak serves not only as the center of horse racing but also as a cultural symbol for the people of Tanah Datar. The land dispute at the racetrack, caused by economic interests, boundary uncertainties, and weak administrative oversight in 2017, culminated in the cancellation of horse racing activities. Although races resumed the following year, the government’s unresolved determination of the boundary remains a challenge for the sustainability of pacu kuda as an alek nagari in the future.